1991
DOI: 10.1902/jop.1991.62.7.458
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Short‐Term Application of a Combination of Platelet‐Derived and Insulin‐Like Growth Factors on Periodontal Wound Healing

Abstract: Polypeptide growth factors are a class of potent natural biologic mediators which regulate many of the activities of wound healing including cell proliferation, migration, and metabolism. Platelet-derived growth factor (PDGF) and insulin-like growth factor-I (IGF-I) have been shown to regulate DNA and protein synthesis in bone cells in vitro and to interact synergistically to enhance soft tissue wound healing in vivo. We have hypothesized that the combination of PDGF and IGF-I may, therefore, enhance regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
257
3
11

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(276 citation statements)
references
References 25 publications
5
257
3
11
Order By: Relevance
“…The use of PDGF-BB in water-soluble carriers such as methylcellulose gels for bone regenerative therapy has several limitations, the greatest of which is the rapid clearance observed in vivo, which results in an inability to maintain a therapeutic concentration over time. Lynch et al 22) noted that the half-life of topically applied PDGF-BB at the wound site was −4 hours, and that >96% had cleared within 96 hours. Taking this into consideration, in an in vitro study, Bateman et al 23) investigated whether a β-TCP scaffold could deliver a consistent dose of PDGF-BB over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of PDGF-BB in water-soluble carriers such as methylcellulose gels for bone regenerative therapy has several limitations, the greatest of which is the rapid clearance observed in vivo, which results in an inability to maintain a therapeutic concentration over time. Lynch et al 22) noted that the half-life of topically applied PDGF-BB at the wound site was −4 hours, and that >96% had cleared within 96 hours. Taking this into consideration, in an in vitro study, Bateman et al 23) investigated whether a β-TCP scaffold could deliver a consistent dose of PDGF-BB over time.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that PDGF-BB increased residual periodontal ligament cells, which 21) , who evaluated the effect of PDGF-BB in postoperative periodontal tissue wound healing and reported that it promoted PDL fibroblast proliferation in expanded polytetrafluoroethylene membrane-protected fenestration defects in dogs. This suggests that PDGF-BB plays a critical role in mitosis and modulation of proliferation of periodontal ligament cells, thus facilitating the wound healing process and inducing formation of new cementum and bone 22) . Histological observation of samples from the experimental groups revealed that the bone and cementum areas gradually increased in size between Table 3 Percentage of mean new bone area at 2 to 8 weeks 2-8 weeks after grafting, and that this increase was clearly greater in both the L-TCP(O)-and S-TCP(G)-particle groups.…”
Section: Discussionmentioning
confidence: 99%
“…PDGF-BB is the most effective on PDL cell mitogenesis and matrix biosynthesis [75,76]. Several preclinical studies were performed using the combination of PDGF-BB and IGF-I for periodontal and peri-implant bone regeneration [77][78][79][80][81][82], culminating in the first study in humans using growth factors for periodontal regeneration [83]. In a human Phase I/II clinical trial, PDGF/IGF-I were considered safe when applied topically to periodontal osseous lesions, resulting in a significant improvement in bone growth and fill of periodontal defects, compared with standard therapy [83].…”
Section: Growth Factor Applications For Oral and Periodontal Tissue Ementioning
confidence: 99%
“…In vivo study also showed that PDGF-BB enhances periodontal regeneration in beagle dogs [9] and non-human primates [10] as well as bone defect fill in a human clinical trial [11,12]. Due to its capability in promoting wound healing [13] through enhancing the formation of granulation tissues, recombinant human PDGF-BB has been approved by US Food and Drug Administration (FDA) for use in diabetic foot ulcers [14].…”
Section: Introductionmentioning
confidence: 99%